Micellar structures of PAAc/PAAm block copolymers in the processes of doxorubicin encapsulation. (24th July 2018) - Kunitskaya, L.; Zheltonozhskaya, T.; Destarac, M.; Mazieres, S.; Klymchuk, D.
Abstract: Micelle formation of asymmetric block copolymers PAAc- b -PAAm (DBC) and PAAm- b -PAAc- b -PAAm (TBC) comprised poly(acrylic acid) and polyacrylamide were investigated. A steady increase in the critical micellization concentration and the Gibbs free micellization energy of the block copolymers at PAAm block lengthening was observed in every series, thus implying the growth of micelle stability. The existence of two morphological forms of micelles was found and discussed. The encapsulation capability of DBC and TBC micelles with respect to doxorubicin (Dox) is reduced at the increase in PAAm block length. The decrease in the Dox encapsulation degree at the pH lowering is stipulated by a strong stabilization of micellar structures.